2002
DOI: 10.1016/s0735-1097(02)02569-x
|View full text |Cite
|
Sign up to set email alerts
|

Interventricular and intraventricular dyssynchrony in idiopathic dilated cardiomyopathy

Abstract: Intraventricular dyssynchrony evaluated with phase analysis of radionuclide angiography is an independent predictor of cardiac event in IDC. The prognosis is related to intraventricular rather than to interventricular dyssynchrony in IDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(33 citation statements)
references
References 23 publications
4
28
0
1
Order By: Relevance
“…In our study, we decided to consider hospitalizations for unstable angina or arrhythmias as worsening HF events, as both conditions may be related to increased filling pressures that may lead to subendocardial ischemia and arrhythmias. We confirmed the data of a recent study (20) that nicely showed that the presence of intra-LV asynchrony is an independent factor of worsening HF and mortality. However, we provided further data on correlations between the QRS width and morphology with the degree and type of ventricular asynchrony.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we decided to consider hospitalizations for unstable angina or arrhythmias as worsening HF events, as both conditions may be related to increased filling pressures that may lead to subendocardial ischemia and arrhythmias. We confirmed the data of a recent study (20) that nicely showed that the presence of intra-LV asynchrony is an independent factor of worsening HF and mortality. However, we provided further data on correlations between the QRS width and morphology with the degree and type of ventricular asynchrony.…”
Section: Discussionsupporting
confidence: 91%
“…However, we provided further data on correlations between the QRS width and morphology with the degree and type of ventricular asynchrony. In addition, we used a noninvasive technique, whereas Fauchier et al (20) used a radionuclide technique coupled with the Fourier analysis. Prolonged ventricular activation, as shown by a wide QRS complex, is common in patients with dilated cardiomyopathy (21,22) and independently impaired systolic and diastolic LV function (8,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…10 Fauchier et al have shown that the prognosis of patients with DCM is related to intraventricular rather than inter-ventricular dysynchrony. 11 In our study, the phase images from POOL-SPECT enabled us to easily visualize inter-and intraventricular asynchrony. The patients with both tended to have more deteriorated cardiac function, and experience more fatal cardiac events ( Table 2).…”
Section: Discussionmentioning
confidence: 86%
“…Tournoux et al (2007) [16] looked at the true deformation of the two LV walls, but may have not fully represented the total LV mechanical dyssynchrony because there may be heterogeneous myocardial deformation, especially in ischemic cardiomyopathy. The data of Fauchier et al (2002) [27] study nicely showed that the presence of mechanical intraventricular dyssynchrony is an independent factor of worsening HF and mortality and it was inconsistent with ischemic group. Similarly, in ischemic patients it was observed in this present series that QRS duration had insignificant correlation with mechanical interventricular dyssynchrony, TPS-SD, TS-SD and TMinMax.…”
Section: Discussionmentioning
confidence: 92%